If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1Dwight + 2x = 0 Solving 1ghitwD + 2x = 0 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-2x' to each side of the equation. 1ghitwD + 2x + -2x = 0 + -2x Combine like terms: 2x + -2x = 0 1ghitwD + 0 = 0 + -2x 1ghitwD = 0 + -2x Remove the zero: 1ghitwD = -2x Divide each side by '1hitwD'. g = -2h-1i-1t-1w-1xD-1 Simplifying g = -2h-1i-1t-1w-1xD-1
| 3(m-3)=0 | | 7m-2=0 | | 11x-5x+6x=168 | | -73+29= | | 2x+11=3x+11 | | 7ab(a+5b+ab-6^2)= | | 6z+18=z | | 2(4a+5)=1.8a-3 | | 2(5-4x)=-46 | | 29-9x=-5(7x+2)-5(-4-5x) | | 2x+11=2x-19 | | -8m-24=24 | | 5-2(y-5)=267 | | y+6n=6n+5 | | 40x=60y | | 4z+11=2z+7 | | 5y+6=-y+24 | | 42-14x=-5(6x+2)-5(-8-3x) | | 2(3a+1)=12+2(4a+3) | | 8-5x-4=-6x+6 | | 3m-4=20 | | 25*x^2-16*x^2= | | Y+14=10 | | x^0+1=0 | | 14x-12+30=4 | | 8z-9=90 | | 2z+y=4z+11 | | z=6z+18 | | 8z-9=1z+9 | | (4x-2)=(4x+10) | | 3x+2m+x+3m+2= | | 7.5(a+1.6)=29.25 |